2022
DOI: 10.3390/atmos13081317
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a Prospective Technology for Building-Integrated Production of Broccoli Microgreens

Abstract: Indoor Vertical Farms (IVF) can contribute to urban circular food systems by reducing food waste and increasing resource use efficiency. They are also known for high energy consumption but could potentially be improved by integration with buildings. Here, we aim to quantify the environmental performance of a prospective building-integrated urban farm. We performed a Life Cycle Assessment for a unit installed in a university campus in Portugal, producing broccoli microgreens for salads. This technology integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…An emerging issue in recent years is preventing food waste by extending the shelf life [21]. New biological and biochemical preservation technologies include optimal storage conditions, various preservation technologies, and smart food labeling [22,23] that can extend shelf life and reduce food waste [24]. However, despite the increasing awareness of reshaping the everyday food-consumption practices at the level of individuals and households, it is estimated that 17% of food is wasted at the retail and consumer levels [25].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging issue in recent years is preventing food waste by extending the shelf life [21]. New biological and biochemical preservation technologies include optimal storage conditions, various preservation technologies, and smart food labeling [22,23] that can extend shelf life and reduce food waste [24]. However, despite the increasing awareness of reshaping the everyday food-consumption practices at the level of individuals and households, it is estimated that 17% of food is wasted at the retail and consumer levels [25].…”
Section: Introductionmentioning
confidence: 99%
“…Through numerous plant physiological sensors, ZigBee technology captures the complete development process of plant germination, growth, blooming, and fruit and delivers the information record to the computer for information processing to ensure nutritional content (Dou, 2022; Yan et al ., 2021; Balamurugan et al ., 2020). IoT is projected to be a key differentiator in the food and farming industries as this invisible technology works behind the scenes, reacting dynamically to how people want “things” to behave to improve food safety (Liu et al ., 2016; Parkes et al ., 2022; Ruan et al ., 2020; Brewster et al ., 2017).…”
Section: Results and Analysismentioning
confidence: 99%
“…Feedback from these tests will be used for final validation of the hydroponic platform components. Thus, it is very important to analyze the factors that influenced the production results and the quality of microgreens (Parkes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Microgreens can be successfully grown in operational (Langenfeld et al, 2022) and semi-controlled environmental conditions (Parkes et al, 2022), identified by controlling specific environmental parameters (Avgoustaki et al, 2020) such as air temperature, relative humidity, substrate, water and light incidence and others. These comparative tests can be used to carry out detailed analyzes by varying some experimental factors, such as the seeding density, the management of environmental conditions (Samuoliene et al, 2012; Sabzalian et al, 2014;Brazaityte et al, 2016) and, respectively, the improvement of IT management programs (Lobiuc et al, 2017) or platforms used for the production of microgreens in one's own kitchen.…”
Section: Discussionmentioning
confidence: 99%